Since it's an arithmetic sequence,
![a_2 = a_1 + d](https://img.qammunity.org/2023/formulas/mathematics/high-school/gnc5ira98qeqgca167566nqmbhps11h867.png)
![a_3 = a_2 + d = a_1 + 2d](https://img.qammunity.org/2023/formulas/mathematics/high-school/2bujcjc3zuciujia5rcqf1nj30w5z8cbl8.png)
![a_4 = a_3 + d = a_1 + 3d](https://img.qammunity.org/2023/formulas/mathematics/high-school/a7luuciqnqpkxyodjii6ph0oavqayxeh7t.png)
and so on, up to
![a_n = a_1 + (n-1)d](https://img.qammunity.org/2023/formulas/mathematics/high-school/m0caa7q5av29b70tu089kjdp23qn34nayu.png)
Now, by substitution,
![a_1 + a_3 + a_5 = -12](https://img.qammunity.org/2023/formulas/mathematics/high-school/8ltr3su10lkh01zmp6pw1dbw6f7vfgzf2t.png)
![a_1 + (a_1+2d) + (a_1+4d) = -12](https://img.qammunity.org/2023/formulas/mathematics/high-school/n2lg7i0zmgtmf8r559rqznj9fdbmo51jnd.png)
![3a_1 + 6d = -12](https://img.qammunity.org/2023/formulas/mathematics/high-school/exzomppbgoi5qkpjq1rw2dmxk230vl0kbs.png)
![a_1 + 2d = -4](https://img.qammunity.org/2023/formulas/mathematics/high-school/24did021bbhwhca8dvjtm7cqx51hjblwm4.png)
![\implies a_1 = -4-2d, a_3 = -4, a_5 = -4+2d](https://img.qammunity.org/2023/formulas/mathematics/high-school/t6bwf9tyh44y7jwe8lb8qdw6l5673e7kfe.png)
Then the product
depends only on d, so that
![(-4-2d) * (-4) * (-4+2d) = 80](https://img.qammunity.org/2023/formulas/mathematics/high-school/tnsrvd1rdzuqgb1nbhp9y5s3obwt2t6qax.png)
Solve for d :
![(4+2d) (4-2d) = -20](https://img.qammunity.org/2023/formulas/mathematics/high-school/bvtye6gw3hcc04g0wvhxzomcqn2m2vh7lc.png)
![16 - 4d^2 = -20](https://img.qammunity.org/2023/formulas/mathematics/high-school/3bssjmwkxxqd1oywxhvl9xv360lj1xqzry.png)
![4d^2 = 36](https://img.qammunity.org/2023/formulas/mathematics/high-school/okmo25c5rgtalgwaxwkhh7ukvogbnsjz56.png)
![d^2 = 9](https://img.qammunity.org/2023/formulas/mathematics/high-school/7ymrw3qqphetrfah3r1quf4kcc4vvvr89i.png)
![d = \pm3](https://img.qammunity.org/2023/formulas/mathematics/high-school/yv8u7zdbrfifn6mq072pi16qngwrt75que.png)
If d = 3, then the first term in the sequence is
, and the tenth term would be
.
If d = -3, then the first term would instead by
, and the tenth term would be
.